2022
DOI: 10.3389/fpls.2022.876192
|View full text |Cite
|
Sign up to set email alerts
|

Increased Carbon Partitioning to Secondary Metabolites Under Phosphorus Deficiency in Glycyrrhiza uralensis Fisch. Is Modulated by Plant Growth Stage and Arbuscular Mycorrhizal Symbiosis

Abstract: Phosphorus (P) is one of the macronutrients limiting plant growth. Plants regulate carbon (C) allocation and partitioning to cope with P deficiency, while such strategy could potentially be influenced by plant growth stage and arbuscular mycorrhizal (AM) symbiosis. In a greenhouse pot experiment using licorice (Glycyrrhiza uralensis) as the host plant, we investigated C allocation belowground and partitioning in roots of P-limited plants in comparison with P-sufficient plants under different mycorrhization sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“… 25 , 34 By altering these pathways, the plant’s defenses against M. oryzae may be strengthened by a boost in the synthesis of secondary metabolites with antimicrobial qualities. 71 , 72 Furthermore, a targeted strategy is provided by using genetic engineering to modify genes linked to defense and carbon allocation. Long-lasting and sustainable solutions can be achieved by creating rice varieties with increased resistance through the optimization of carbon utilization pathways.…”
Section: Strategies For Mitigating Rice Blast Disease By Controlling ...mentioning
confidence: 99%
“… 25 , 34 By altering these pathways, the plant’s defenses against M. oryzae may be strengthened by a boost in the synthesis of secondary metabolites with antimicrobial qualities. 71 , 72 Furthermore, a targeted strategy is provided by using genetic engineering to modify genes linked to defense and carbon allocation. Long-lasting and sustainable solutions can be achieved by creating rice varieties with increased resistance through the optimization of carbon utilization pathways.…”
Section: Strategies For Mitigating Rice Blast Disease By Controlling ...mentioning
confidence: 99%
“…Arbuscular mycorrhizal (AM) fungi can establish symbiotic associations with the majority of terrestrial plants (Wang and Qiu, 2006). In this relationship, plants supply lipids and sugars to AM fungi (Jiang et al, 2017), while the AM fungi aid plants in the absorption of mineral nutrients and water (Li et al, 2013;Li et al, 2014;Xie et al, 2019;Xie et al, 2022). A large number of studies have shown that AM fungi play an active role in helping plants cope with a wide range of abiotic stresses (Malhi et al, 2021), such as drought (Li et al, 2013;Li et al, 2014), heavy metals (Wu et al, 2015;Li et al, 2018), and salt-alkali (Santander et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…), a perennial medicinal plant primarily grown in the arid loess plateau where P is usually a limiting macronutrient, require more P for nitrogen (N)-fixation (Zhong et al, 2023). In particular, licorice demands high P in the early growth stages (Xie et al, 2022). However, there is limited understanding regarding the potential of Bacillus megaterium to induce resistance to low P in licorice.…”
Section: Introductionmentioning
confidence: 99%